Experimental evaluation of hybrid software engineering methodology for embedded firmware development on intelligent mobile robot - Abang Jawawi, Dayang Norhayati; Deris, Safaai; Mamat, Rosbi; Mohamed, Radziah (Faculty of Computer Science and Information System, 2004)
Software development process for real-time embedded systems differs from the development of software for traditional data processing systems, due to non-functional requirements such as reliability and timing constraints. Therefore, appropriate equipment and methodologies are needed for real-time embedded software development. Based on the development of control software development for a wall-climbing robot, developed at Universiti Teknologi Malaysia, faced problems using only one software development methodology. Based on the study, a hybrid methodology has been proposed. This software engineering methodology is tested on wall-climbing robots using hardware-in-loop simulation and as a result of testing demonstrates the efficacy of using a hybrid methodology that can produce a software that meets the requirements. However, some issues still need to be answered and further measurements need to be made to test the efficacy of the hybrid methodology, in the actual embedded system. A smart moving robot has been developed to make the basis for the immersive real-time system. The two main outputs of the research were the results of the assessment of the strengths and weaknesses of the software engineering methodology and the phases of the identified methodology to be automated.